2008
DOI: 10.1111/j.1365-2362.2008.02051.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy in type 2 diabetes mellitus is associated with increased intima‐media thickness and endothelial dysfunction

Abstract: DR is associated with increased IMT and endothelial dysfunction in T2DM. Impaired endothelial function may be a common denominator of pathogenesis of microvascular complications and atherosclerosis in T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 35 publications
3
35
1
Order By: Relevance
“…Diabetic microvascular disease may be associated with subclinical atherosclerosis, as indicated by the increased cardiovascular mortality associated with the presence of microvascular complications [23]. Some previous studies [6][7][8][9] investigated the relation between carotid IMT and plaque with diabetic retinopathy. Two of them [6,7] reported independent associations of carotid IMT with diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Diabetic microvascular disease may be associated with subclinical atherosclerosis, as indicated by the increased cardiovascular mortality associated with the presence of microvascular complications [23]. Some previous studies [6][7][8][9] investigated the relation between carotid IMT and plaque with diabetic retinopathy. Two of them [6,7] reported independent associations of carotid IMT with diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 98%
“…Some previous studies [6][7][8][9] investigated the relation between carotid IMT and plaque with diabetic retinopathy. Two of them [6,7] reported independent associations of carotid IMT with diabetic retinopathy. However, another study [8] did not demonstrate independent associations between diabetic retinopathy and CCA or ICA-IMT and with carotid stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AI was strongly associated with retinopathy even after adjusting for all above parameters except age and duration of diabetes [19]. A similar association between retinopathy and increased CIMT was reported in type 2 diabetes in the work of Malecki et al [20]. Recently, Cardoso et al demonstrated that increased central arterial stiffness measured by pulse wave velocity (PWV) is associated with the presence of microvascular complications (retinopathy and peripheral neuropathy) independently of other established determinants of aortic stiffness [21].…”
Section: Discussionmentioning
confidence: 52%